1973
DOI: 10.2151/jmsj1965.51.1_29
|View full text |Cite
|
Sign up to set email alerts
|

On the Stability of Ekman Boundary Layer Flow with Thermally Unstable Stratification

Abstract: An investigation is made of the stability of the Ekman boundary layer flow with a thermally unstable stratification based on perturbation analysis. Three different types of the instability associated with the flow may be found, preference of which depends on Reynolds number, and Richardson number. The thermal instability, which is of gravitational origin modified by the shear flow, is dominant for Ri*10-3, while the other two, which are of inertial origin modified by the thermal stratification, are found for R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1980
1980
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…The application of the convective instability findings to geophysical secondary flows using the eddy viscosity analogy was immediately evident for convective cloud streets such as those in Figure 1. Kuo [1963], Asai and Nakasuji [1973], and Deardorff [1972] found linear vortices in their solutions for unstably stratified PBL flow. Pioneering work on finite amplitude cellular convection was done by Malkus and Veronis [1958], using the nonlinear techniques described by Stuart [1958Stuart [ , 1971.…”
Section: The Results Show That Inflection Point Instabilities Occur Atmentioning
confidence: 99%
“…The application of the convective instability findings to geophysical secondary flows using the eddy viscosity analogy was immediately evident for convective cloud streets such as those in Figure 1. Kuo [1963], Asai and Nakasuji [1973], and Deardorff [1972] found linear vortices in their solutions for unstably stratified PBL flow. Pioneering work on finite amplitude cellular convection was done by Malkus and Veronis [1958], using the nonlinear techniques described by Stuart [1958Stuart [ , 1971.…”
Section: The Results Show That Inflection Point Instabilities Occur Atmentioning
confidence: 99%
“…In this configuration they found that convective rolls may be aligned north-south or east-west, depending on the parameter values characterizing the system. The interaction of Ekman instabilities and convection or stable stratification is also important in the planetary boundary layer (see Etling 1971;Brown 1972;Asai & Nakasuji 1973;Wipperman, Etling & Kirstein 1978; also the review Etling & Brown 1993). …”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have investigated the structures of the thermal-shear instability for constant values of the vertical wind shear and 2 (< 0) (Hill 1968;Asai 1970), or an unstably stratified Ekman boundary layer (Asai and Nakasuji 1973). These approaches agreed on roll-shaped and shear-parallel structures as the fastest-growing mode.…”
Section: Linear Stability Analysesmentioning
confidence: 99%